Lunar Reconnaissance Orbiter Mission 2009
DOI: 10.1007/978-1-4419-6391-8_7
|View full text |Cite
|
Sign up to set email alerts
|

The Lunar Reconnaissance Orbiter Diviner Lunar Radiometer Experiment

Abstract: The Diviner Lunar Radiometer Experiment on NASA's Lunar Reconnaissance Orbiter will be the first instrument to systematically map the global thermal state of the Moon and its diurnal and seasonal variability. Diviner will measure reflected solar and emitted infrared radiation in nine spectral channels with wavelengths ranging from 0.3 to 400 microns. The resulting measurements will enable characterization of the lunar thermal environment, mapping surface properties such as thermal inertia, rock abundance and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 18 publications
0
71
0
1
Order By: Relevance
“…Abundant secondary craters from the Orientale basin cover the south polar area [Spudis et al, 2009]. Both polar regions contain large amounts of permanently shadowed terrain, thought on the basis of theory to be very cold (less than 100 K) [Vasavada et al, 1999;Paige et al, 2010a] and subsequently shown from Diviner data to be as cold as 25 K in some areas [Paige et al, 2010b] and thus, are located where water ice might be stable for geologically long periods of time (>1 Ga) [Vasavada et al, 1999].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant secondary craters from the Orientale basin cover the south polar area [Spudis et al, 2009]. Both polar regions contain large amounts of permanently shadowed terrain, thought on the basis of theory to be very cold (less than 100 K) [Vasavada et al, 1999;Paige et al, 2010a] and subsequently shown from Diviner data to be as cold as 25 K in some areas [Paige et al, 2010b] and thus, are located where water ice might be stable for geologically long periods of time (>1 Ga) [Vasavada et al, 1999].…”
Section: Resultsmentioning
confidence: 99%
“…The LRO Diviner thermal emission spectrometer on LRO mapped surface temperatures over the course of several years, yielding mean annual surface temperature maps [Paige et al, 2010a[Paige et al, , 2010b. This mapping shows large areas near both poles with surface temperatures less than 104 K, the temperature below which water is permanently stable Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Using our model, we can compute the temporal variation in the surface temperature from a given set of parameters, such as the grain size and density of the material. By comparing the diurnal temperature profile based on [33][34][35] For asteroids, a thermal infrared imager (TIR) onboard the Hayabusa2 spacecraft is planning to observe asteroid 162173 Ryugu. 36 TIR measurements will play an important role in estimating the grain size on the surface of Ryugu, and subsequently to judge the potential sites for touchdown and regolith sample collection by the Hayabusa2 spacecraft.…”
Section: Applications Of Developed Thermal Conductivity Modelmentioning
confidence: 99%
“…Surface temperature is considered equivalent to brightness temperature because the moon soil emissivity in the wavelengths of the three channels is considered equal to 1. This condition is verified by the high correlation between the different channels (Paige et al 2010). …”
Section: Temperature Mapsmentioning
confidence: 57%
“…The first one allows the generation and update of one pre-processed set of 3D-grid data containing an aggregation of all brightness temperature measurements from LRO DLRE (Paige et al 2010) in three thermal channels (7, 8 and 9) of the instrument since the beginning of the observations. These three brightness temperature values provided in DLRE RDR tables in the NASA PDS supply the 3D-grid established with a predefined time step and spatial resolution for a typical lunar day on the whole moon surface, excluding the effect of eclipses and other incoherent data (filtered using quality flags).…”
Section: Temperature Mapsmentioning
confidence: 99%